Self-adaptive sweating cooling thermal protection structure and manufacturing method
By adopting conventional runner layer, lattice structure layer and surface microflower layer in the sweat-induced cooling structure, and using SLM additive process and femtosecond laser processing technology, the problem of immature multi-stage runner structure design and preparation technology in the prior art is solved, and efficient thermal protection is achieved in ultra-high temperature environments.
Patent Information
- Application Number
- CN202411917035.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-29
AI Technical Summary
The existing sweat-induced cooling heat protection structures have poor thermal protection effects in ultra-high temperature environments. The main reason is that the multi-stage runner structure design and preparation technology are immature, and the flow path distribution and size controllability are low, which leads to difficulty in transporting cooling media.
Adaptive sweating cooling structure is adopted, including conventional runner layer, lattice structure layer and surface microflower layer. Through SLM additive process and femtosecond laser processing technology, the active sweating characteristics of three-stage cooling runner coupling are achieved.
It realizes stable thermal protection in ultra-high temperature environments, improves cooling capacity and controllability of runner structure, and reduces production costs and complexity.
Smart Images

Figure CN119898466A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adaptive sweating cooling heat protection structure and a manufacturing method thereof, belonging to the technical field of adaptive sweating cooling heat protection components. Background Art
[0002] For aircraft nose cones, wings or fusion reactor divertors and other components, due to the influence of ultra-high temperatures during service, they may need to withstand a maximum of ≥4-5MW / m 2 The extreme heat flux density has brought great challenges to the safe service of spacecraft and fusion reactors. In order to achieve the purpose of long-term and repeated use of spacecraft and fusion reactors, non-ablative thermal protection methods must be adopted to ensure the safety and reliability of the leading edge of the spacecraft and the divertor of the fusion reactor.
[0003] Transpiration cooling is an efficient and highly potential active thermal protection method. Its mechanism of action is: the cooling medium is driven by capillary force through a multi-stage flow channel structure to undergo transport, heat exchange, phase change and other processes, and forms a layer of air film protection on the surface of the component to isolate the ultra-high temperature heat flow generated by the friction between the air and the component. The sweating cooling thermal protection scheme has two main advantages: 1) It has a stronger cooling capacity. The main reason is that liquids with large specific heat capacity (such as water) are generally selected as cooling media, which can absorb more heat during its phase change process; 2) The sweating cooling thermal protection adopts a multi-stage transport flow channel similar to leaves, which can autonomously transport the cooling medium under the action of capillary force, without the need for additional power devices, and further achieves the purpose of weight reduction. However, in actual use, the sweating cooling thermal protection scheme did not achieve the desired effect. Relevant studies have found that the main reason for the reduction in thermal protection effect is that the design and preparation technology of the multi-stage flow channel structure are immature, and the flow channel distribution and size controllability are low, resulting in difficulty in cooling medium transportation.
[0004] At present, the processing methods for sweating cooling multi-stage flow channel structure are powder sintering, layer etching, additive manufacturing and femtosecond laser processing. The powder sintering method prepares porous media by sintering spherical metal powder or composite materials, and the flow channel distribution and size cannot be controlled. The layer structure is to etch the flow channel on the thin plate, and then diffuse weld it layer by layer. The flow channel is controllable, but the design and processing of complex flow channels are not effective and the cost is high. Compared with the first two, the additive manufacturing method can realize the construction of flow channels on demand, but the forming limit is difficult to meet the sweating requirements of the cooling medium. Femtosecond laser can be used to prepare diameters of 10μm to 100μm, but due to limitations such as materials, its depth-to-diameter ratio is only 1:10 to 1:20, and it is difficult to use for the processing of complex multi-stage flow channels.
[0005] So far, many scholars have devoted themselves to the innovation and improvement of the structural form of transpiration cooling. For example, Professor Wang Jianhua of the University of Science and Technology of China proposed a structural scheme in which several porous areas are arranged at intervals along the incoming flow direction (Rui Ding, Jianhua Wang, Fei He, Guangqi Dong, Longsheng Tang. Numerical investigation on the performances of porous matrix with transpiration and film cooling [J]. Applied Thermal Engineering, 2019, 146: 422-431.). At the same time, Professor Wang also proposed a transpiration structure scheme with variable porosity distribution (Nan Wu, Jianhua Wang, Fei He, Liang Chen, Bangcheng Ai, Optimization transpiration cooling of nose cone with non-uniform permeability [J], International Journal of Heat and Mass Transfer, 2018, 127: 882-891.). However, the above two configurations are only used for calculation and simulation analysis of the effects of transpiration cooling, and do not involve specific structural schemes and preparation processes. Professor Xu Ruina of Tsinghua University designed a self-pumping transpiration cooling system based on the principle of tree transpiration using sintered bronze and hydrophilic silicate aluminum fiber (Gan Huang, Zhiyuan Liao, Ruina Xu, Yinhai Zhu, Pei-Xue Jiang. Self-pumping transpiration cooling with a protective porous armor[J], Applied Thermal Engineering, 2020, 164: 114485). However, the system is composed of multiple parts and is not an integrated manufacturing structure. Although the system verifies the principle of self-pumping transpiration, the problem of sintering multi-stage flow channel control has not been solved, and it is difficult to achieve engineering application. Previously, our factory proposed a new type of three-stage flow channel transpiration cooling structure, which was integrated by electron beam additive technology and femtosecond laser processing. The structure consists of three parts: a conventional flow channel layer, a sintered powder layer, and a surface micro-flow channel layer. However, due to the precision of the preparation process and the inherent shortcomings of the sintered powder, the application effect of the structure is not ideal.The main problems are: 1) The electron beam additive process has low forming accuracy and cannot realize structures such as closed cavities. Complex components must be formed in an integrated manner through welding; 2) The sintered powder layer flow channel has low controllability and differences in liquid-solid forming, resulting in low interface bonding strength.
[0006] In order to overcome the above problems and realize the stable operation of the thermal protection system of the leading edge of the spacecraft and the divertor of the fusion reactor, it is urgently necessary to propose an adaptive sweating cooling thermal protection structure with good stability, low control difficulty and high forming accuracy and a new manufacturing method thereof, which has the advantages of on-demand construction of SLM additive manufacturing and the high precision of femtosecond laser. Summary of the invention
[0007] The technical problem solved by the present invention is: to overcome the shortcomings of the prior art, to provide an adaptive sweating cooling thermal protection structure and a manufacturing method, to achieve the active sweating characteristics of three-stage cooling channel coupling, and to be applicable to the thermal protection requirements of ultra-high temperature service environments.
[0008] The technical solution of the present invention is:
[0009] The present invention discloses an adaptive sweating cooling structure, comprising: a conventional flow channel layer, a lattice structure layer and a surface micro-flow channel layer; wherein the conventional flow channel layer, the lattice structure layer and the surface micro-flow channel layer are connected in sequence; the conventional flow channel layer, the lattice structure layer and the surface micro-flow channel layer respectively contain dendritic fractals, three-dimensional variable density lattices, and micro-scale sweating channels; the conventional flow channel layer, the lattice structure layer and the surface micro-flow channel layer are all metallurgically bonded, and the dendritic fractal channels, three-dimensional variable density lattices and micro-scale sweating channels are interconnected.
[0010] Furthermore, in the above structure, the density of the conventional channel layer and the surface microchannel layer is ≥99%; the lattice structure layer is filled with variable density lattices; and the equivalent diameter of the variable density lattices changes continuously within the range of 200-600 μm.
[0011] Furthermore, in the above structure, the diameter of the flow channel of the surface micro-channel layer does not exceed 100 μm; and the diameter of the flow channel of the conventional channel layer does not exceed 20 mm.
[0012] Furthermore, in the above structure, the three-dimensional variable density lattice is composed of one or two of body-centered cubic lattice BCC, face-centered cubic lattice FCC, and three-periodic minimal surface TMPS structure, and the cell size, rod diameter or wall thickness of the three-dimensional variable density lattice changes continuously.
[0013] The invention discloses a method for manufacturing an adaptive sweating cooling structure, comprising:
[0014] S1, pre-treating the powder;
[0015] S2. Simulate the residual stress and deformation during the structural additive process to determine the sweating structure printing model;
[0016] S3, using SLM additive manufacturing process, according to the sweating structure printing model, using pre-treated powder, printing to obtain a sample with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer;
[0017] S4. Perform wire cutting, stress relief annealing, support removal and non-destructive testing on the sample in sequence; polish the inner and outer surfaces of the sample to remove sintering powder or impurities on the surface of the component to obtain a machined sample;
[0018] S5. Use femtosecond laser processing technology to punch holes on the surface of the machined sample to prepare a series of micro-channels, perform micro-structural treatment on the surface of the component after punching, and obtain a self-sweating cooling structure sample;
[0019] S6. Conduct nondestructive testing on the self-sucking sweat cooling structure samples to determine the size, accuracy and surface quality of the components and internal flow channels;
[0020] S7. If the size, precision and surface quality of the component and the internal flow channel meet the requirements, the final transpiring cooling heat protection component is obtained; otherwise, repeat steps S4 to S6.
[0021] Furthermore, in the above method, the powder is pretreated, specifically:
[0022] The metal powder material is subjected to vacuum low-temperature drying treatment until the powder fluidity is 15-20s / 50g;
[0023] The processed powder raw material is loaded into the SLM additive equipment.
[0024] Furthermore, in the above method, the sweat structure printing model is printed using the pretreated powder to obtain a sample having a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer, specifically:
[0025] T1. Add support structure to the sweating structure printing model;
[0026] T2. Select a metal sheet that is compatible with the pre-treated powder raw material as the forming substrate;
[0027] T3, slicing the printed model of the sweating structure after adding the support structure to form a sliced model;
[0028] T4. Evenly spread a layer of pre-treated powder on the molding substrate, set corresponding process parameters and scanning strategies for the slicing model, and selectively melt the pre-treated powder according to the slicing model;
[0029] T5. Repeat T3 to T4 until a sample with a conventional flow channel layer, a lattice structure layer, and a surface microfluidic channel layer is obtained.
[0030] Furthermore, in the above method, the material of the adaptive sweating cooling structure is nickel-based high-temperature alloy, high-strength steel, high-temperature titanium alloy or multi-principal component alloy; the nickel-based high-temperature alloy is GH4099 or GH4251; the high-strength steel is 18NI-300 maraging steel; the high-temperature titanium alloy is Ti65 titanium alloy; the multi-principal component alloy is NiCoCr medium-entropy alloy or NbMoTaW high-entropy alloy.
[0031] Furthermore, in the above method, the process parameters of the SLM additive process are: laser power 200-300W, scanning speed 900-1200mm / s, overlap spacing 40-60μm, powder thickness 30-40μm, and layer-by-layer rotation 60°~80°.
[0032] Furthermore, in the above method, the process parameters of the femtosecond laser processing process are: laser spot diameter is 10-30 μm, laser parameters are pulse width is 600-900 fs, laser wavelength is 800-1200 nm, single pulse energy is 20-50 μJ, repetition frequency is 300-500 kHz, and scanning rate is 500-700 mm / s.
[0033] The beneficial effects of the present invention and the prior art are:
[0034] (1) The rod diameter or wall thickness of the lattice structure used in the present invention is continuously changed, and the preparation method can realize continuous variable density forming. This structure is closer to the plant water transport structure and is a better bionic structure.
[0035] (2) Compared with the electron beam selection process, the SLM process used in the present invention is simpler, has lower cost, is highly controllable, can realize closed structure forming, and is more suitable for large-scale production;
[0036] (3) The lattice structure of the present invention and the conventional flow channel layer and the surface micro-flow channel layer are all metallurgically bonded by melting and solidification, and have higher strength. In addition, the lattice structure itself is composed of rods or thin walls formed by melting powder, and its own structural performance is better.
[0037] (4) The present invention can prepare a variable density active sweating component with a multi-stage flow channel structure, which can be applied to the thermal protection requirements of ultra-high temperature service environments, such as the leading edge of a high-speed aircraft or a fusion reactor divertor.
[0038] (5) Based on the previous research on the preparation of sweating cooling structure by electron beam additive powder sintering, the present invention proposes to use a variable density lattice structure to replace the powder sintering structure, and combines SLM technology and femtosecond laser processing technology. By controlling the laser selective melting additive melting process and femtosecond laser processing process, the technical problems of low multi-stage flow channel distribution and dimensional controllability and low interface bonding strength are solved, and high-precision forming and control of the multi-stage flow channel structure are achieved, laying a technical foundation for the manufacture and processing of sweating active thermal protection components for high-speed aircraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a planar structural diagram of the self-sucking sweating cooling of the present invention;
[0040] Figure 2 It is a process flow chart of the present invention;
[0041] Figure 3 This is a structural diagram of the self-sucking sweating cooling curved surface of the present invention;
[0042] Figure 4 The diagram is a schematic diagram of the self-sucking sweat cooling planar structure of the present invention; (a) is before water injection, and (b) is after water injection. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0044] like Figure 1 As shown, the present invention discloses an adaptive sweating cooling structure, comprising: a conventional flow channel layer, a lattice structure layer and a surface microfluidic layer; wherein the conventional flow channel layer, the lattice structure layer and the surface microfluidic layer are connected in sequence; the conventional flow channel layer, the lattice structure layer and the surface microfluidic layer contain dendritic fractals, three-dimensional variable density lattices, and microscale sweating channels respectively, the conventional flow channel layer, the lattice structure layer and the surface microfluidic layer are all metallurgically bonded, and the dendritic fractal channels, the three-dimensional variable density lattices and the microscale sweating channels are interconnected.
[0045] Preferably, the density of the conventional flow channel layer and the surface micro-flow channel layer is ≥99%; the lattice structure layer is filled with variable density lattices; and the equivalent diameter of the variable density lattices changes continuously within the range of 200-600 μm.
[0046] Preferably, the diameter of the flow channel of the surface microchannel layer does not exceed 100 μm; and the diameter of the flow channel of the conventional channel layer does not exceed 20 mm.
[0047] Preferably, the three-dimensional variable density lattice is composed of one or two of a body-centered cubic lattice BCC, a face-centered cubic lattice FCC, and a three-periodic minimal surface TMPS structure, and the cell size, rod diameter or wall thickness of the three-dimensional variable density lattice changes continuously.
[0048] like Figure 2 As shown, the present invention discloses a method for manufacturing an adaptive sweating cooling structure, comprising:
[0049] S1, pre-treating the powder;
[0050] S2. Simulate the residual stress and deformation during the structural additive process to determine the sweating structure printing model;
[0051] S3, using SLM additive manufacturing process, according to the sweating structure printing model, using pre-treated powder, printing to obtain a sample with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer;
[0052] S4. Perform wire cutting, stress relief annealing, support removal and non-destructive testing on the sample in sequence; polish the inner and outer surfaces of the sample to remove sintering powder or impurities on the surface of the component to obtain a machined sample;
[0053] S5. Use femtosecond laser processing technology to punch holes on the surface of the machined sample to prepare a series of micro-channels, perform micro-structural treatment on the surface of the component after punching, and obtain a self-sweating cooling structure sample;
[0054] S6. Conduct nondestructive testing on the self-sucking sweat cooling structure samples to determine the size, accuracy and surface quality of the components and internal flow channels;
[0055] S7. If the size, precision and surface quality of the component and the internal flow channel meet the requirements, the final transpiring cooling heat protection component is obtained; otherwise, repeat steps S4 to S6.
[0056] Preferably, the powder is pretreated, specifically:
[0057] The metal powder material is subjected to vacuum low-temperature drying treatment until the powder fluidity is 15-20s / 50g;
[0058] The processed powder raw material is loaded into the SLM additive equipment.
[0059] Preferably, according to the sweating structure printing model, the pretreated powder is used for printing to obtain a sample having a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer, specifically:
[0060] T1. Add support structure to the sweating structure printing model;
[0061] T2. Select a metal sheet that is compatible with the pre-treated powder raw material as the forming substrate;
[0062] T3, slicing the printed model of the sweating structure after adding the support structure to form a sliced model;
[0063] T4. Evenly spread a layer of pre-treated powder on the molding substrate, set corresponding process parameters and scanning strategies for the slicing model, and selectively melt the pre-treated powder according to the slicing model;
[0064] T5. Repeat T3 to T4 until a sample with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer is obtained.
[0065] Preferably, the material of the adaptive sweating cooling structure is nickel-based high-temperature alloy, high-strength steel, high-temperature titanium alloy or multi-principal component alloy; the nickel-based high-temperature alloy is GH4099 or GH4251; the high-strength steel is 18NI-300 maraging steel; the high-temperature titanium alloy is Ti65 titanium alloy; the multi-principal component alloy is NiCoCr medium-entropy alloy or NbMoTaW high-entropy alloy.
[0066] Preferably, the process parameters of the SLM additive process are: laser power 200-300 W, scanning speed 900-1200 mm / s, overlap spacing 40-60 μm, powder thickness 30-40 μm, and layer-by-layer rotation 60° to 80°.
[0067] Preferably, the process parameters of the femtosecond laser processing process are: laser spot diameter is 10-30 μm, laser parameters are pulse width is 600-900 fs, laser wavelength is 800-1200 nm, single pulse energy is 20-50 μJ, repetition frequency is 300-500 kHz, and scanning rate is 500-700 mm / s.
[0068] Example 1
[0069] This embodiment proposes an adaptive sweating cooling structure and manufacturing method, which prepares a self-sucking sweating cooling flat plate structure based on laser selective melting (SLM) technology and femtosecond laser micro-nano technology. This structure is GH4251 nickel-based high-temperature alloy. The D10 of the GH4251 powder is 15-20μm, D50 is 30-35μm, D90 is 48-55μm, fluidity (Hall flow rate) is ≤20s / 50g, and the bulk density is ≥4.6g / cm 3 .
[0070] First, the preparation method of laser selective melting of self-suction sweating cooling flat plate structure:
[0071] S1. First, the required GH4251 metal powder material is vacuum-dried at low temperature (inert gas, 150°C, 2h) to improve the powder fluidity. The treated powder raw materials are loaded into the SLM equipment, and the nickel-based high-temperature alloy is selected as the molding substrate. The SLM equipment is debugged and prepared for 3D printing.
[0072] S2. In an inert gas environment, the substrate of the SLM equipment is preheated at a temperature of 100°C; GH4251 nickel-based high-temperature alloy powder is spread on the preheated substrate, and then the powder in the powder layer is selectively melted according to the slicing model.
[0073] S3. Repeat the spreading and melting of high-temperature alloy powder on the surface of the formed layer until the printing is completed. Use the powder cleaning equipment to remove the excess metal powder in the conventional flow channel and variable density lattice; then perform non-destructive testing, solid solution treatment, support removal, aging treatment, machining, grinding and other treatments to obtain a self-sucking sweat cooling structure with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer.
[0074] The laser selective melting process parameters in step S2 are: laser power 250-350 W, line speed 800-1000 mm / s, overlap spacing 60-80 μm, and powder layer thickness 40-60 μm.
[0075] Heat treatment process parameters in step S3:
[0076] (1) Solution treatment: 1150-1200℃, 1-2h, gas quenching;
[0077] (2) Aging treatment: 800-850℃, 6-8h, furnace cooling.
[0078] Then, femtosecond laser drilling is performed. The femtosecond laser processing preparation method is as follows:
[0079] T1. Fix the self-sucking sweat cooling structure sample on the processing platform to ensure that the sample will not move during the drilling process;
[0080] T2. Set all operating parameters of the femtosecond laser drilling equipment;
[0081] T3. Use femtosecond laser drilling equipment to perform laser drilling at a fixed position on the surface of the self-sweating cooling structure sample. Ensure that the laser beam is perpendicular to the surface of the component processing position.
[0082] T4. Surface microstructure processing: Set all operating parameters of the femtosecond laser equipment, and use the femtosecond laser equipment to process the surface of the component to form a hydrophilic microstructure to facilitate the spreading of the cooling medium.
[0083] The femtosecond laser drilling process parameters in step T3 are as follows: the laser spot diameter is 20 μm, the laser parameters are a pulse width of 800 fs, a laser wavelength of 1030 nm, a single pulse energy of 20 to 30 μJ, a repetition frequency of 600 kHz, and a scanning rate of 600 mm / s.
[0084] The femtosecond laser microstructure processing parameters in step T4 are as follows: the laser spot diameter is 20 μm, the laser parameters are a pulse width of 800 fs, a laser wavelength of 1030 nm, a single pulse energy of 20 to 30 μJ, a repetition frequency of 400 kHz, and a scanning rate of 600 mm / s.
[0085] Example 2
[0086] Example 2 A self-sucking sweating cooling planar structure is prepared by using the laser selective melting (SLM) and femtosecond laser micro-nano technology proposed in the present invention. The material is Ti65 high-temperature titanium alloy. The D10 of Ti65 high-temperature titanium alloy powder is 15-20 μm, D50 is 30-35 μm, D90 is 50-55 μm, fluidity (Hall flow rate) is ≤20s / 50g, and the bulk density is ≥3.0g / cm 3 .
[0087] First, the self-suction sweating cooling planar structure SLM preparation method:
[0088] S1. First, the required Ti65 powder is vacuum-dried at low temperature (inert gas, 150°C, 2h) to improve the powder fluidity. The treated powder raw materials are loaded into the SLM equipment, TC4 titanium alloy is selected as the molding substrate, the SLM equipment is debugged, and 3D printing is prepared.
[0089] S2. In an inert gas environment, preheat the substrate of the SLM equipment at a preheating temperature of 150°C; spread Ti65 powder on the preheated substrate and selectively melt the powder according to the slicing model.
[0090] S3. Repeat the processes of spreading powder and melting on the surface of the melted powder layer until the printing is completed. Use the powder cleaning equipment to remove the excess metal powder in the conventional flow channel and the variable density lattice; then perform non-destructive testing, stress relief annealing, support removal, machining, grinding, etc. on the adaptive sweating cooling structure sample to obtain an adaptive sweating cooling flat plate structure with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer.
[0091] The SLM process parameters in step S2 are: power 180-250 W, scanning speed 700-1000 mm / s, overlap spacing 70-100 μm, and powder thickness 30 μm.
[0092] Stress relief annealing process parameters in step S3: vacuum environment,
[0093] (1) Solution treatment: 900-1000℃, 2-3h, cooling.
[0094] (2) Aging treatment: 700-800℃, 4-8h, air cooling.
[0095] Then, femtosecond laser drilling is performed. The femtosecond laser processing preparation method is as follows:
[0096] T1. Fix the self-sucking sweat cooling structure sample on the processing platform to ensure that the sample will not move during the drilling process;
[0097] T2. Set all operating parameters of the femtosecond laser drilling equipment;
[0098] T3. Use femtosecond laser drilling equipment to perform laser drilling at a fixed position on the surface of the self-sweating cooling structure sample. Ensure that the laser beam is perpendicular to the surface of the sample processing position.
[0099] T4. Surface microstructure processing: Set all operating parameters of the femtosecond laser equipment, and use the femtosecond laser equipment to process the surface of the sample to form a hydrophilic microstructure to facilitate the spreading of the cooling medium.
[0100] The femtosecond laser drilling process parameters in step T3 are as follows: the laser spot diameter is 20 μm, the laser parameters are a pulse width of 800 fs, a laser wavelength of 1030 nm, a single pulse energy of 40-50 μJ, a repetition frequency of 600 kHz, and a scanning rate of 600 mm / s.
[0101] The femtosecond laser microstructure processing parameters in step T4 are as follows: the laser spot diameter is 20 μm, the laser parameters are pulse width is 800 fs, laser wavelength is 1030 nm, single pulse energy is 40-50 μJ, repetition frequency is 400 kHz, and scanning rate is 600 mm / s.
[0102] Example 3
[0103] Example 3: A surface structure suitable for adaptive sweating cooling is prepared by using the laser selective melting (SLM) technology and femtosecond laser micro-nano technology proposed in the present invention. The material is 18IN-300 aged martensitic high-strength steel. The D10 of the powder is 15-20 μm, the D50 is 30-35 μm, the D90 is 45-50 μm, the fluidity (Hall flow rate) is ≤20 s / 50 g, and the bulk density is ≥4.0 g / cm 3 .
[0104] First, the SLM preparation method of the adaptive sweating cooling surface structure:
[0105] S1. First, the required 18IN-300 powder is vacuum-dried at low temperature (inert gas, 120°C, 2h) to improve the powder fluidity. The treated powder raw materials are loaded into the SLM equipment, 316L stainless steel is selected as the molding substrate, the SLM equipment is debugged, and 3D printing is prepared.
[0106] S2. In an argon environment, 18IN-300 powder is evenly spread on a stainless steel substrate, and then the powder is selectively melted according to the slice model.
[0107] S3. Repeat the processes of powder spreading and melting on the surface of the formed layer until the printing is completed. Use the powder cleaning equipment to remove the excess metal powder in the conventional flow channel and the variable density three-dimensional lattice; then perform non-destructive testing, solid solution, support removal, aging, machining, grinding, etc. on the adaptive sweating cooling curved surface structure sample to obtain an adaptive sweating cooling curved surface structure sample with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer.
[0108] The SLM additive process parameters for the surface and internal areas in step S2 were as follows: laser power 200-300 W, scanning speed 900-1200 mm / s, overlap spacing 40-60 μm, powder thickness 30-40 μm, and layer-by-layer rotation 67°.
[0109] Heat treatment process parameters in step S3:
[0110] (1) Solution treatment: vacuum environment, 800-900℃, 2-4h;
[0111] (2) Aging treatment: 400-550℃, 8-16h, air cooling.
[0112] Then, femtosecond laser drilling is performed. The femtosecond laser processing preparation method is as follows:
[0113] T1. Fix the adaptive sweat cooling curved surface structure sample on the processing platform to ensure that the sample will not move during the drilling process;
[0114] T2. Set all operating parameters of the femtosecond laser drilling equipment;
[0115] T3. Use femtosecond laser drilling equipment to perform laser drilling at a fixed position on the surface of the adaptive sweating cooling curved surface structure. Ensure that the laser beam is perpendicular to the surface of the sample processing position.
[0116] T4. Surface microstructure processing: Set all operating parameters of the femtosecond laser equipment, and use the femtosecond laser equipment to process the surface of the sample to form a hydrophilic microstructure to facilitate the spreading of the cooling medium.
[0117] The femtosecond laser drilling process parameters in step T3 are as follows: the laser spot diameter is 20 μm, the laser parameters are a pulse width of 800 fs, a laser wavelength of 1030 nm, a single pulse energy of 30-50 μJ, a repetition frequency of 600 kHz, and a scanning rate of 600 mm / s.
[0118] The femtosecond laser microstructure processing parameters in step T4 are as follows: the laser spot diameter is 20 μm, the laser parameters are pulse width is 800 fs, laser wavelength is 1030 nm, single pulse energy is 30-50 μJ, repetition frequency is 400 kHz, and scanning rate is 600 mm / s.
[0119] like Figure 3 As shown, this is a diagram of the self-sucking sweat cooling curved surface structure of the present invention; Figure 4 The following is a diagram showing the effect of the self-sucking sweat cooling plane structure. (a) is before water injection, and (b) is after water injection.
[0120] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
[0121] The contents not described in detail in the specification of the present invention belong to the common knowledge of the professionals in this field.
Claims
1. An adaptive sweating cooling structure, characterized in that: include: A conventional flow channel layer, a lattice structure layer and a surface micro-flow channel layer; wherein the conventional flow channel layer, the lattice structure layer and the surface micro-flow channel layer are connected in sequence; The conventional channel layer, lattice structure layer and surface microchannel layer contain dendritic fractals, three-dimensional variable density lattices and microscale sweating channels respectively. The conventional channel layer, lattice structure layer and surface microchannel layer are all metallurgically bonded, and the dendritic fractal channels, three-dimensional variable density lattices and microscale sweating channels are interconnected.
2. The adaptive sweating cooling structure according to claim 1, characterized in that: The density of the conventional flow channel layer and the surface micro-flow channel layer is ≥99%; the lattice structure layer is filled with variable density lattices; and the equivalent diameter of the variable density lattices changes continuously within the range of 200-600 μm.
3. The adaptive sweating cooling structure according to claim 1, characterized in that: The diameter of the flow channel of the surface micro-channel layer does not exceed 100 μm; the diameter of the flow channel of the conventional channel layer does not exceed 20 mm.
4. A method for manufacturing an adaptive sweating cooling structure according to claim 1, characterized in that: The three-dimensional variable density lattice is composed of one or two of a body-centered cubic lattice BCC, a face-centered cubic lattice FCC, and a three-periodic minimal surface TMPS structure, and the cell size, rod diameter or wall thickness of the three-dimensional variable density lattice changes continuously.
5. A method for manufacturing an adaptive sweating cooling structure, characterized in that: include: S1, pre-treating the powder; S2. Simulate the residual stress and deformation during the structural additive process to determine the sweating structure printing model; S3, using SLM additive manufacturing process, according to the sweating structure printing model, using pre-treated powder, printing to obtain a sample with a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer; S4. Perform wire cutting, stress relief annealing, support removal and non-destructive testing on the sample in sequence; polish the inner and outer surfaces of the sample to remove sintering powder or impurities on the surface of the component to obtain a machined sample; S5. Use femtosecond laser processing technology to punch holes on the surface of the machined sample to prepare a series of micro-channels, perform micro-structural treatment on the surface of the component after punching, and obtain a self-sweating cooling structure sample; S6. Conduct nondestructive testing on the self-sucking sweat cooling structure samples to determine the size, accuracy and surface quality of the components and internal flow channels; S7. If the size, precision and surface quality of the component and the internal flow channel meet the requirements, the final transpiring cooling heat protection component is obtained; otherwise, repeat steps S4 to S6.
6. The method for manufacturing an adaptive sweating cooling structure according to claim 5, characterized in that: The powder is pretreated, specifically: The metal powder material is subjected to vacuum low-temperature drying treatment until the powder fluidity is 15-20s / 50g; The processed powder raw material is loaded into the SLM additive equipment.
7. The method for manufacturing an adaptive sweating cooling structure according to claim 5, characterized in that: The sweating structure printing model is printed using the pretreated powder to obtain a sample having a conventional flow channel layer, a lattice structure layer, and a surface micro-flow channel layer, specifically: T1. Add support structure to the sweating structure printing model; T2. Select a metal sheet that is compatible with the pre-treated powder raw material as the forming substrate; T3, slicing the printed model of the sweating structure after adding the support structure to form a sliced model; T4. Evenly spread a layer of pre-treated powder on the molding substrate, set corresponding process parameters and scanning strategies for the slicing model, and selectively melt the pre-treated powder according to the slicing model; T5. Repeat T3 to T4 until a sample with a conventional flow channel layer, a lattice structure layer, and a surface microfluidic channel layer is obtained.
8. The method for manufacturing an adaptive sweating cooling structure according to claim 7, characterized in that: The material of the adaptive sweating cooling structure is nickel-based high-temperature alloy, high-strength steel, high-temperature titanium alloy or multi-principal component alloy; the nickel-based high-temperature alloy is GH4099 or GH4251; the high-strength steel is 18NI-300 maraging steel; the high-temperature titanium alloy is Ti65 titanium alloy; the multi-principal component alloy is NiCoCr medium-entropy alloy or NbMoTaW high-entropy alloy.
9. The method for manufacturing an adaptive sweating cooling structure according to claim 5, characterized in that: The process parameters of the SLM additive process are: laser power 200-300W, scanning speed 900-1200mm / s, overlap spacing 40-60μm, powder thickness 30-40μm, and layer-by-layer rotation 60°~80°.
10. The method for manufacturing an adaptive sweating cooling structure according to claim 5, characterized in that: The process parameters of the femtosecond laser processing process are: laser spot diameter is 10-30 μm, laser parameters are pulse width is 600-900 fs, laser wavelength is 800-1200 nm, single pulse energy is 20-50 μJ, repetition frequency is 300-500 kHz, and scanning rate is 500-700 mm / s.